Effectiveness of Android Based Arabic Learning to Improve Mufradat and Qawa'id Learning Achievements - Suluri (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2019)
This research was conducted with the aim of knowing: 1) the effectiveness of android-based Arabic language learning media in improving learning achievement of mufradat and qawa'id, 2) differences in the improvement of student learning outcomes using android-based media with students who do not use android-based media. This research is a reseach and development (RnD) study. Samples were taken using the pretest technique. The treatment in this study was in the form of android-based media use in the experimental group and without android-based media in the control group. Learning outcomes data were obtained from posttest. This study produced several findings, namely: 1) effective android-based media to improve learning achievement mufradat and qawa'id, 2) there are differences in Arabic learning outcomes of students using android-based media with students who do not use android-based media.